2007
DOI: 10.1177/0038038507076618
|View full text |Cite
|
Sign up to set email alerts
|

Parental Divorce and Children's Socio-economic Success: Conditional Effects of Parental Resources Prior to Divorce, and Gender of the Child

Abstract: Both the level and allocation of pre-divorce parental and family resources may be impor tant predictors for the effects of divorce on child outcomes. This study estimates specific divorce effects on socio-economic outcomes of children in families having a different amount and allocation of both cultural and economic resources. In addition, this study tests whether general divorce effects differ between boys and girls. Data are used from the Family Sur vey Dutch Population 1998 (FSDP98) and the Family Sur vey D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
1
31
0
6
Order By: Relevance
“…Other studies have reported the opposite pattern, indicating that children from disadvantaged families suffered less from divorce than their privileged counterparts (Bernardi & Radl, 2014;Fischer, 2007). This evidence supports the notion of "divorce as an equalizer."…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Other studies have reported the opposite pattern, indicating that children from disadvantaged families suffered less from divorce than their privileged counterparts (Bernardi & Radl, 2014;Fischer, 2007). This evidence supports the notion of "divorce as an equalizer."…”
Section: Introductionsupporting
confidence: 68%
“…Previous research on heterogeneous effects of divorce has almost exclusively focused on child outcomes (Augustine, 2014;Bernardi & Radl, 2014;Grätz, 2015;Fischer, 2007;Mandemakers & Kalmijn, 2014). Yet, these analysts have invoked contrasting assumptions about changes occurring at the parental level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As dificuldades econômicas que surgem após a dissolução marital 27,28 parecem ter impacto significativo na redução dos níveis de bem-estar e sucesso acadêmico da criança 29,30 . As mudanças financeiras têm impacto direto, mas também indireto, sobre a criança.…”
Section: Problemas Financeirosunclassified
“…ex. : viver em bairros com problemas), mudar de escola e ter menos oportunidades educacionais, interferindo na sua realização acadêmica 30,31 . Tendencialmente, os pais que ficam com a guarda sentem um acentuado declínio nos recursos econômicos disponíveis para responder às necessidades da família.…”
Section: Problemas Financeirosunclassified